PERMASALAHAN SISTEM PENGEMBANGAN FRANCHISE ATAU WARALABA (STUDY KASUS MENANTEA) - i, Urbanisasi; subagijo, kevin putra (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research discusses the development and marketing strategy of the "Menantea" franchise business in the midst of intense competition with other franchise business competitors in urban areas. This research uses normative research methods that use literature as a data source. The purpose of this paper is if franchise law protects the rights of brand owners and franchisors, and regulates the contractual relationship between the two. The potential for development and appropriate marketing strategies as well as a good understanding of franchise law can be a guideline for other franchise businesses to face competition in urban areas.